The mental health care model in Brazil: analyses of the funding, governance processes, and mechanisms of assessment - Thiago Lavras Trapé; Rosana Onocko Campos
ABSTRACT OBJECTIVE This study aims to analyze the current status of the mental health care model of the Brazilian Unified Health System, according to its funding, governance processes, and mechanisms of assessment. METHODS We have carried out a documentary analysis of the ordinances, technical reports, conference reports, normative resolutions, and decrees from 2009 to 2014. RESULTS This is a time of consolidation of the psychosocial model, with expansion of the health care network and inversion of the funding for community services with a strong emphasis on the area of crack cocaine and other drugs. Mental health is an underfunded area within the chronically underfunded Brazilian Unified Health System. The governance model constrains the progress of essential services, which creates the need for the incorporation of a process of regionalization of the management. The mechanisms of assessment are not incorporated into the health policy in the bureaucratic field. CONCLUSIONS There is a need to expand the global funding of the area of health, specifically mental health, which has been shown to be a successful policy. The current focus of the policy seems to be archaic in relation to the precepts of the psychosocial model. Mechanisms of assessment need to be expanded.